Characterization of human tibrovirus envelope glycoproteins - Munyeku-Bazitama, Yannick; Saito, Takeshi; Hattori, Takanari; Miyamoto, Hiroko; Lombe, Boniface Pongombo; Mori-Kajihara, Akina; Kajihara, Masahiro; Muyembe-Tamfum, Jean-Jacques; Igarashi, Manabu; Park, Eun-sil; Morikawa, Shigeru; Makiala-Mandanda, Sheila; et al. (Journal of Virology, 2024)
Human tibroviruses are poorly characterized emerging rhabdoviruses associated with either asymptomatic infection or severe disease with a case fatality rate as high as 60% in humans. However, the extent and burden of human infection as well as factors behind differences in infection outcomes are largely unknown. In this study, we characterized human tibrovirus glycoproteins, which play a key role in virus-host interactions, mainly focusing on their structural and antigenic differences and cellular tropism. Our results provide critical information for understanding the biological properties of these novel viruses and for developing appropriate preparedness interventions such as diagnostic tools, vaccines, and effective therapies.